2012
DOI: 10.1590/s0004-282x2012000600005
|View full text |Cite
|
Sign up to set email alerts
|

Jaw-opening oromandibular dystonia secondary to Wilson's Disease treated with botulinum toxin type A

Abstract: We have reported a case series of five patients with jaw-opening oromandibular dystonia secondary to Wilson's disease (WD), in which the patients were treated with botulinum toxin type A (BTX-A). In all cases, dystonia score was partially reduced three weeks after injections. The most common side effect was transient mild dysphagia. This preliminary study showed that jaw-opening oromandibular dystonia in WD may be partially responsive to the use of BTX-A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In cases not responding to pharmacological therapy, neurosurgical treatment should be considered. [6,24,27,37] The pharmacological agents used in the treatment of dystonia include (1) anticholinergics, (2) baclofen, (3) benzodiazepines, (4) dopaminergic compounds (levodopa or dopamine agonists), (5) dopamine-depleting drugs, and (6) antiepileptic drugs (carbamazepine/oxcarbamazepine). [24,28] The data on the efficacy of this kind of treatment in patients with WD are limited but encouraging.…”
Section: [32]mentioning
confidence: 99%
See 1 more Smart Citation
“…In cases not responding to pharmacological therapy, neurosurgical treatment should be considered. [6,24,27,37] The pharmacological agents used in the treatment of dystonia include (1) anticholinergics, (2) baclofen, (3) benzodiazepines, (4) dopaminergic compounds (levodopa or dopamine agonists), (5) dopamine-depleting drugs, and (6) antiepileptic drugs (carbamazepine/oxcarbamazepine). [24,28] The data on the efficacy of this kind of treatment in patients with WD are limited but encouraging.…”
Section: [32]mentioning
confidence: 99%
“…BTX injections used in focal dystonias were effective in 8/9 patients with WD (the remaining patient had a slight improvement), as reported separately by three different centers. [32,[37][38][39] In the case of dystonia affecting more body regions (i.e. segmental, multisegmental, or generalized dystonia), there are only few published reports on treatment of symptoms.…”
Section: [32]mentioning
confidence: 99%
“…The pathophysiology and etiology of jaw-opening dystonia remain unclear, but some possible pathophysiological mechanisms or peripheral causes have been suggested for some cases [2,4]. Moreover, in some cases, the jaw-opening dystonia presumably had a central origin, e.g., focal brain lesion, ischemic stroke, neurodegenerative disease, or metabolic or genetic disorders with structural brain involvement [10][11][12][13][14][15][16][17]. However, secondary jaw-opening dystonia associated with a central lesion is extremely rare, and psychogenic (functional) movement disorder initially presenting as jaw-opening dystonia has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Type A BT (BTA) has proved effective for various forms of dystonia [6] , particularly, blepharospasm [7] , [8] , [9] , cervical dystonia [10] , oromandibular dystonia [11] , [12] , bucolingual dyskinesia [13] and laryngeal dystonia [14] , [15] . Several studies have confirmed its long-term efficacy [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%